Analysis and sequence of the speB gene encoding agmatine ureohydrolase, a putrescine biosynthetic enzyme in Escherichia coli. - Szumanski, M B (1990)
The speB gene of Escherichia coli encodes the enzyme agmatine ureohydrolase (AUH). AUH catalyzes the hydrolysis of agmatine to urea and putrescine in one of the two polyamine biosynthetic pathways in E. coli. Sequencing of a 2.97-kilobase-pair fragment of the E. coli chromosome containing speB revealed the presence of three intact open reading frames (ORFs), ORF1 and ORF2 on one strand and ORF3 on the opposite strand, as well as a truncated ORF, ORF4, which terminated 92 kilobase pairs upstream from ORF3. ORF3 contained the coding sequence of the speB gene, as confirmed by complementation analysis. Two ORF3 transcripts were detected: a shorter transcript that included only ORF3 and a longer transcript that included both ORF3 and ORF4. The short transcript was abundantly expressed when the ORF4 sequences were deleted, but when ORF4 and its upstream sequences were present, the polycistronic message predominated and the amount of the monocistronic message was drastically reduced. The promoter from which the shorter transcript was produced contained a TATACT sequence at position -12, but sequences upstream from the -12 position seemed to be irrelevant for promoter activity. The predicted amino acid sequence of AUH contained three regions of high homology to the arginases of yeasts, rats, and humans.